Epidemiological and Clinicopathological Trends of Breast Cancer in Chinese Patients During 1993 to 2013: A Retrospective Study. Issue 26 (July 2015) - Si, Wen; Li, Ying; Han, Yingjie; Zhang, Fan; Wang, Yingzhe; Li, Ying; Linghu, Rui Xia; Zhang, Xingyang; Yang, Junlan
Abstract : Abstract: This study aimed to summarize the epidemiological and pathological trends of breast cancer in Chinese women. The clinical data of 4968 breast cancer patients treated at the Chinese PLA General Hospital from 1993 to 2013 were retrospectively reviewed. The mean ± standard deviation (SD) age was 47.4 ± 11.3 years before the year 2001, 49.2 ± 11.2 years during 2001 to 2010, and 50.6 ± 11.4 years after the year 2010, respectively ( P  < 0.001). The ratio of premenopausal women to postmenopausal women was 1.6 and no significant changes were found during the period ( P  = 0.121). The proportion of patients with Scarff Bloom Richardson III breast cancer showed significant increase along with time ( P  = 0.015). The breast cancer was accounting for 31.7% at stage I and DCIS/LCIS and tend to be diagnosed with early stage around time ( P  < 0.001). The proportion of DCIS/LCIS and stage I increased with time during the 20 years from 14.6% to 33.2%, whereas the proportion of stage III to IV decreased. The proportion of Luminal A-like subtype gradually reduced and Luminal B-like (HER2-negative) increased and developed to the predominant type. Older age and earlier stage at diagnosis, as well as the alternation of predominant molecular subtypes, have become the developed trends of breast cancer. Abstract : Supplemental Digital Content is available in the text